Reflections on global policy documents and the WHO's infant feeding guidelines: lessons learnt - Sellen Daniel W; de Paoli Marina M; van Esterik Penny; Blystad Astrid; Leshabari Sebalda C; Moland Karen Marie I (BMC, 2010)
Abstract As the papers in this thematic series have illustrated, the postnatal prevention of mother to child transmission of HIV (PMTCT) strategy has struggled with lack of local relevance. In an attempt to increase our understanding of the great dissonance between the policy intention and the experiences of the participants in concrete PMTCT programmes, we will in these concluding remarks draw upon writings in institutional ethnography. Through the concept of 'global texts' we reflect upon the scientific and ideological underpinnings of the WHO policy guidelines on HIV and infant feeding, and the influence that this policy has had across multiple local settings. The particular impact of the global postnatal PMTCT policy guidelines on the position of breastfeeding lies at the core of the discussion.